JUMPA Vol.2 No.2 Juni 2015 PENGARUH PERSEPSI MASYARAKAT, CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP MINAT BELI ASURANSI: PENGARUH PERSEPSI MASYARAKAT, CITRA MEREK DAN KUALITAS PELAYANAN TERHADAP MINAT BELI ASURANSI - Sutar STIE Muhammadiyah Jakarta (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2015)
The purpose of this study was to determine the influence of public perception, brand image and Qulaity services to buying interest at PT. Asuransi Raksa Pratikara Jakarta. The research method is descriptive qualitative research method, the data collection is done by using a questionnaire to respondents, insurance customers Raksa Pratikara. Hipotesis used are Ho1 hypothesis, allegedly there is influence between the public perception of the insurance buying interest . Ho2 hypothesis, Allegedly there is the influence of brand image with the insurance buying interest. Ho3, Allegedly there is influence between services with insurance buying interest raksa. Model of analysis used is multiple linear regression analysis by SPSS-17 approach in processing the data. From these results it can be concluded that partial public perception, brand image and service positive and significant impact on the insurance buying interest Raksa Pratikara. R Square value of 0.65 which means that the influence of variable public perception, brand image and service affect the insurance buying interest by 65 percent and the remaining 35 percent influenced by other factors. In partial assay results t1 count is greater than t table which means that people's perceptions significantly influence buying interest insurance, test results t2 count is greater than t table which means the brand image significantly influence buying interest insurance Raksa Pratikara and t3 count is greater than t table service which means a significant effect on the insurance buying interest Raksa Pratikara.